The Association of Obesity and the Antiaging Humoral Factor Klotho in Middle-Aged and Older Adults - Carlos H. Orces (The Scientific World Journal)
Objectives. Previous studies have reported conflicting results regarding the relationship between obesity and the antiaging humoral factor klotho. Thus, the present study aimed to examine the association of anthropometric measurements, weight history change, and vitamin D status with serum klotho levels. Methods. The National Health and Nutrition Examination Survey data were used to compare sex-specific logarithm transformed serum klotho levels across standardized anthropometric measurements and weight change history in subjects aged 40–79 years. The baseline measured height, and self-reported weight were used to calculate the body mass index (BMI) at two-time intervals: age 25 and ten years before the measured BMI. Subjects were then categorized as never obese, obese to nonobese, nonobese to obese, and always obese. Results. Of 4,971 participants, the prevalence of general obesity was 41%, and abdominal obesity (waist circumference ≥88 cm) was present in 75% of women. Overall, lower serum klotho levels were seen in older adults, men, nonsmokers, alcohol users, and those with an estimated glomerular filtration rate (eGFR) < 60 ml/min. Multivariate models demonstrated that general and abdominal obesity in women was inversely associated with serum klotho levels. Moreover, women who developed obesity from age 25 and ten years before the baseline BMI had significantly lower mean klotho levels at 765.0 and 757.4 pg/ml compared with 820.5 pg/ml (p<0.05) among those that were never obese, respectively. In contrast, serum klotho levels did not significantly differ among men, irrespective of their weight history. In a subanalysis, higher klotho levels were seen in participants with an adequate vitamin D status (≥50 nmol/L) than their overweight and obese counterparts (p<0.05). Conclusions. Obesity among women was significantly and inversely associated with serum klotho levels. Similarly, women who developed obesity during their lifetime had consistently lower klotho levels than their never-obese counterparts.